The Sexual Behaviors of University Students from Papua in Surabaya - Giyai, Maria Clara (Health Notions, 2017)
Sexuality is not unfamiliar topic for us in recent day. It is  due to the sexuality can not be dissociated from human lifes, moreoverr in this globalization era where information easily accessed through internet. There is also a thought tendencies especially teenagers have an attemps in sexual behaviors. This observation is concerning with sexual behaviors of university students from Papua in Surabaya. This was an observational study with cross-sectional design.This research was conducted on April 14,2017-Mei 20,2017, at students from Papua in Surabaya. The sample of the study 30 respondents. The data analysis is using chi-square test. the Colleagues whom gladly watch Porn film influence the significant effect, that is 82,6% from 30 respondents. The calculation with chi-square method obtained the value of p<0,05. The influence of collegues is the most significant that is 70% from 30 respondents. From the results of numbers are counted with chi-square method obtained the value of p<0,15 that meaning the Colleagues is the most significant influences. The conclusison for this research is the having friends whom gladly watch the Porn films influence the adequate significant that is 82,6% from  30 respondents and the influence of the Colleague are the most significants that is  70% from 30 respondents.  Keywords: Sexual Behaviors, Students University, Porn Films.